Delamination behavior of lithium-ion battery anodes: Influence of drying temperature during electrode processing. Issue 4 (11th March 2016) - Baunach, M.; Jaiser, S.; Schmelzle, S.; Nirschl, H.; Scharfer, P.; Schabel, W.
ABSTRACT: One essential process step during electrode processing for lithium-ion batteries is the drying of the wet particulate electrode coating. The electrode film solidifies during evaporation of the solvent and a porous film is formed. In this study, we focus on the influence of drying temperature on the internal electrode structure of the dry film. Anode slurries that consist of graphite and an aqueous binder system were coated and subsequently dried. To assure defined and controllable drying conditions, a laboratory set-up with a temperature-controlled substrate carrier and an impingement dryer was used. To facilitate a scale-up to continuously passed dryers, the choice of experimental temperatures was based on a calculation of steady-state temperatures that result from gas temperatures that are commonly applied in industrial drying processes. The delamination behavior of the differently dried electrodes was investigated by means of a 90° peel test. The results show a strong dependency of electrode adhesion on drying temperature. A lower adhesion force at higher temperatures hints at a variation in binder content at the interface between the copper substrate and the coating layer. The formation of a consolidation layer at the air-film interface during drying is identified as a possible explanation and a criterion for consolidation layer formation is suggested.